AKTIVITAS PENGHAMBATAN POLIMERISASI HEM DARI FRAKSI ETIL ASETAT DAUN MANURAN, Coptosapelta tomentosa Valeton ex K.Heyne (Rubiaceae) - Arnida Arnida; Sutomo Sutomo; Lia Rosyidah (Jurnal Fitofarmaka Indonesia, 2019)
Malaria is a serious disease caused by Plasmodium parasites and is transmitted by the salivary glands of female Anopheles mosquito. The manuran (Coptosapelta tomentosa Valeton ex K.Heyne) is empirically used as a malarial treatment. The study aimed to determine the IC50 value of ethyl acetate fraction and the coumpounds contained on the C. tomentosa Valeton ex K. Heyne leaf ethyl acetat fraction. The identification of chemical composition used tube test method. The inhibitory activity of heme polymerization in vitro did by Basillico modified method. The identification of chemical contents on the ethyl acetate fraction of C. tomentosa leaf Valeton ex K. Heyne showed positive results containing flavonoid, tannin, saponin, terpenoid, and anthraquinone. The average percentage heme polymerization inhibition of C. tomentosa valeton ex K. Heyne leaf ethyl acetate fraction respectively from large to small concentrations of 97.94; 96.94; 95.01; 91.63; 86.19; 76.12; and 44.83 %. Result of probit analysis, that it has HPIA IC50 value of 0.252±0.009 mg/mL and chloroquine diphosphate was 0.214±0.012 mg/mL. The independent sample T-test showed that there was significant difference between IC50 value of them. The ethyl acetate fraction of C. tomentosa leaf Valeton ex K. Heyne has heme polymerization inhibition activity.